2023
DOI: 10.1186/s40359-023-01039-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in adolescents: prevalence and its relation to high-risk behaviors among secondary school students in Mbarara Municipality, Uganda

Abstract: Background Psychological distress among adolescents negatively affects their academic performance, relationships with family and friends, and ability to participate fully in the community. Stressful life events in low-income countries and risk-taking behavior of adolescents have raised concerns regarding the impact of psychological distress among adolescents. Therefore, the present study estimated the prevalence of psychological distress and examined the high-risk behaviors associated with psyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Prevalence rates of 40% have been recorded in China ( 19 ), 54% in Saudi Arabia ( 20 ), and 20.6% in Tanzania ( 21 ). Academic stress and adverse life events may account for much of this high prevalence of psychological distress among adolescents ( 22 ). However, a growing number of adolescents now spend a good deal of their time on their mobile phones, leading to an increasing incidence of mobile phone addiction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prevalence rates of 40% have been recorded in China ( 19 ), 54% in Saudi Arabia ( 20 ), and 20.6% in Tanzania ( 21 ). Academic stress and adverse life events may account for much of this high prevalence of psychological distress among adolescents ( 22 ). However, a growing number of adolescents now spend a good deal of their time on their mobile phones, leading to an increasing incidence of mobile phone addiction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…shown prevalence rates of 33.8% for anxiety and 27.2% for depression among students worldwide (10). Numerous studies have identified psychological distress as the most common mental health problem among students, often preceding various psychological disorders and negatively impacting students' learning and academic achievements (11,12). Moreover, the death of a parent can lead to a spectrum of psychological disorders and behavioral issues in students, further resulting in decreased motivational beliefs.…”
Section: Introductionmentioning
confidence: 99%